Group actions on local moduli space of holomorphic vector bundles - Doan, An-Khuong (Canadian mathematical bulletin, 2023)
We prove that actions of complex reductive Lie groups on a holomorphic vector bundle over a complex compact manifold are locally extendable to its local moduli space.